The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/pce.13147
|View full text |Cite
|
Sign up to set email alerts
|

Strigolactones positively regulate chilling tolerance in pea and in Arabidopsis

Abstract: Strigolactones (SL) fulfil important roles in plant development and stress tolerance. Here, we characterized the role of SL in the dark chilling tolerance of pea and Arabidopsis by analysis of mutants that are defective in either SL synthesis or signalling. Pea mutants (rms3, rms4, and rms5) had significantly greater shoot branching with higher leaf chlorophyll a/b ratios and carotenoid contents than the wild type. Exposure to dark chilling significantly decreased shoot fresh weights but increased leaf numbers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(37 citation statements)
references
References 80 publications
(124 reference statements)
0
35
0
1
Order By: Relevance
“…The control over this phenotypic plasticity via SLs indicates that they have the potential to enable plants to avoid deleterious effects from severe drought by reducing vegetative growth and by also saving energy for subsequent reproductive development. By using SL mutants of pea (SL‐synthetic rms3 and SL‐signalling rms4 ) and Arabidopsis (SL‐synthetic max3 and max4 , and SL‐signalling max2 ), Cooper et al () recently demonstrated the roles of SLs in protecting photosynthesis under dark chilling conditions, thereby enhancing shoot biomass production. In addition, SLs also act as a positive regulator of leaf senescence by enabling plants to reallocate the nutrients from old tissues to developing younger tissues (Yamada & Umehara, ).…”
Section: Sls Fine‐tune Plant Architectures Under Abiotic Stressesmentioning
confidence: 99%
See 2 more Smart Citations
“…The control over this phenotypic plasticity via SLs indicates that they have the potential to enable plants to avoid deleterious effects from severe drought by reducing vegetative growth and by also saving energy for subsequent reproductive development. By using SL mutants of pea (SL‐synthetic rms3 and SL‐signalling rms4 ) and Arabidopsis (SL‐synthetic max3 and max4 , and SL‐signalling max2 ), Cooper et al () recently demonstrated the roles of SLs in protecting photosynthesis under dark chilling conditions, thereby enhancing shoot biomass production. In addition, SLs also act as a positive regulator of leaf senescence by enabling plants to reallocate the nutrients from old tissues to developing younger tissues (Yamada & Umehara, ).…”
Section: Sls Fine‐tune Plant Architectures Under Abiotic Stressesmentioning
confidence: 99%
“…Thus, an important area of research has emerged to further elucidate the roles of SLs in plant stress adaptation. Because SLs have already been proven to be responsive to drought, salinity, and chilling (Cooper et al, ; C. V. Ha et al, ; W. Li et al, ; Liu et al, ; Visentin et al, ; Y. Zhang et al, ), it would be interesting to investigate how SLs adjust osmotic imbalance and oxidative stress by regulating the formation of compatible solutes and antioxidant components.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, substantial evidence has demonstrated that SLs and KARs are involved in the regulation of the plant responses to abiotic stress [8,37,38,[41][42][43]46,63,143,190,191] (Table 1). SL levels are finely modulated under various types of abiotic stress.…”
Section: Dynamic Regulation Of Sls Under Abiotic Stressesmentioning
confidence: 99%
“…SLs also promote beneficial symbiotic relationships between host plants and mycorrhizal fungi [35,36]. The biosynthesis and signaling of SLs are regulated by various abiotic stress factors [37][38][39][40], including the recently reported SL involvement in responding to nutrient deprivation, drought, chilling and salinity [38,[40][41][42][43][44][45][46][47][48][49][50]. Such studies provide new insights into the novel roles SL signaling plays in the regulation of plant adaptation to adverse environmental conditions [51][52][53][54].Karrikins (KARs) are found in smoke released from the heating or combustion of plant material, after which they can stimulate the germination of dormant seeds [55][56][57][58].…”
mentioning
confidence: 99%